MATHEMATICAL MODELING OF LIQUID DISTRIBUTION IN BRANCH CAPILLARY SYSTEMS - Yury M. VERNIGOROV; Iosif A. KIPNIS (Advanced Engineering Research, 2010)
Mechanism of forming habit of the plants on basis of assumption that the basic process which enables growth and development of plants is water transmission through their capillary channels is considered.